Neurofeedback: A New Method for Improvement of Crystal Methamphetamine Dependent Patients - Fatemeh Dehghani; Reza Rostami (Drug Control Headquarters, Research and Education Office, 2010)
Objective: The aim of this study was examining the effectiveness of neurofeedback training on general mental health and severity of addiction in Crystal Methamphetamine dependant patients. Method: On this purpose one hundred substance dependant patients undergoing a medicine treatment, were selected in a lumpy way. In pre test stage, all volunteers were assessed with Addiction Severity Index questionnaire and General Health questionnaire (GHQ-28) and were matched on the base of ASI scores. Then they have been assigned in two groups. One group was specified as experimental group by chance, and the other one as control group. In this experimental study with pre-post test design, experimental group received 30 sessions neurofeedback further usual medicine treatment. Control group just received usual medicine. After finishing the term all two experimental and control group's patients were assessed again by those questionnaires. Results: Multivariate analysis of covariance showed that experimental group had a significant difference in general psychological health and addiction severity, in comparison with control group. Conclusion: Therefore neurofeedback training can be used to improve the effectiveness of treatment results in Crystal Methamphetamine dependant patients.